PENETAPAN TEMBAGA (CU) PADA MUARA SUNGAI BONE DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Isa, Ishak (Jurnal Sainstek, 2006)
This research is aimed to know the amount of Cuprum (Cu) in the Bone Rivers delta by its sediment as the sample. This analysist uses the Atomic Absorption Spectrofotometry method. Sample of this research was taken from two places. They were the delta of Bone River and river stream area 50 meters from the delta. This was done to know the source of the Cuprum that comes into the delta. This research shown that the amount of Cuprum in Bone Rivers delta is 0,0449658 ppm than the amount of Cuprum in the river stream area which is 50 meters from the delta where the amount of Cuprum is 0,0445991 ppm. This amount is still in the limit of tolerance, base on the Letters of Decision of Minister of Cuprum in the maritime body is 0,06 ppm.